Transformasi Pembelajaran: Membaca Pemahaman Siswa Melalui Model SQ3R Berbantuan Canva - Faisy, Rifky Alif Nur; Hartatik, Sri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to analyze the improvement in reading comprehension skills of fourth-grade students at SDN Wonokromo I/390 Surabaya by applying the SQ3R model assisted by the Canva application. The research method used is Classroom Action Research (CAR) conducted in two cycles. The data collected includes the results of assessing students' reading comprehension skills from two meetings in each cycle. The data collection techniques used include observation, interviews, and documentation, sourced from primary and secondary data. The primary data obtained are the results of student assessments on reading comprehension materials through the Canva media, while the secondary data come from books, journals, and articles as reference materials. The data analysis was conducted through the processes of data reduction, data display, and conclusion drawing. The research results show that in the first cycle, the average student score was 71.11% in the first meeting and increased to 74.81% in the second meeting, although this improvement did not yet meet the success indicators. After reflection and improvement, in the second cycle, the average student score reached 82.96% in the first meeting and 93.33% in the second meeting, thus it can be stated that the implementation of this method was successful. This study confirms that the use of the SQ3R model with the help of the Canva application is efficacious in improving students' reading comprehension skills, encouraging active engagement, and facilitating a better understanding of the texts read.